Rhizobia induction mechanisms to reduce drought stress in legumes - Santillana, Nery (2021)
Drought is one of the main limitations of agricultural productivity and food security, in Andean mountain. The use of atmospheric nitrogen-fixing rhizobia in symbiosis with legumes, and tolerant to a wide range of adverse conditions, such as drought, is a great potential in sustainable agriculture. The aim of this review is to compile studies about drought stress effect on the legume-rhizobia symbiosis and rhizobia mechanisms to induce drought tolerance in legumes. The search for information was conducted from August to December 2020, using key terms. The drought effect on the nodulation  and atmospheric nitrogen fixation process is made known, as well as the rhizobia ability to synthesize exopolysaccharides, enzymes, phytohormones, siderophores, osmolytes and solubilize phosphates as induction mechanisms to mitigate drought stress in legumes. This review will serve to propose future research using rhizobia to mitigate the drought effect on the legumes cultivation in environments such as the Andean mountains.